2016
DOI: 10.1080/23766808.2016.1230461
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal flowering and pollination of a rare Caribbean sage, Salvia arborescens (Lamiaceae)

Abstract: The phenology, floral biology and pollination ecology of Salvia arborescens Urb. & Ekman (Lamiaceae) are reported, based on field and garden observations. The flowers of S. arborescens are white, fragrant and rich in nectar. Anthesis begins in the late afternoon, and flowers wilt by late morning of the following day. Floral features fit the moth pollination syndrome. S. arborescens flowers are visited by a variety of nocturnal moths in the wild, including Celiptera levinum (Lepidoptera: Noctuoidea: Erebidae), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…To avoid creating a category of butterfly pollination with a single species, and because its pollinator(s) has not been confirmed, we grouped S. whitehousei with the polymorphic group, where other unconfirmed species have been placed. Salvia arborescens from Hispaniola is the only species documented to flower strictly at night and is moth pollinated (Reith and Zona 2016). Because of a lack of morphological information for this species, it was not included it in this study.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid creating a category of butterfly pollination with a single species, and because its pollinator(s) has not been confirmed, we grouped S. whitehousei with the polymorphic group, where other unconfirmed species have been placed. Salvia arborescens from Hispaniola is the only species documented to flower strictly at night and is moth pollinated (Reith and Zona 2016). Because of a lack of morphological information for this species, it was not included it in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The weeds Stachytarpheta cayennensis (Verbenaceae), Commelina diffusa (Commelinaceae), and Salvia palifolia (Lamiaceae), predominant in shaded coffee crops, can be important sources of food due to their variety of attributes such as a long period of profuse flowers and vibrant colors, volumes of nectar and considerable pollen grains, adequate growth for soil protection, and unusual morphologies to attract a variety of pollinators (Barp et al, 2010;De La Vega et al, 2000;Lundgren, 2009;Reith and Zona 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Arévalo et al-Feeding and refuge of beneficial coffee insects pollinators (Barp et al, 2010;De La Vega et al, 2000;Lundgren, 2009;Reith and Zona 2016).…”
Section: Hours Of Higher Activity Of Insects Associatedmentioning
confidence: 99%
“…Among a variety of small, medium-sized, and large bees, melittoid flies (belonging to the bee pollinator guild, Vogel, 2012) have been proven to be effective pollinators of Salvia (Celep et al, 2014). Reith & Zona. (2016) observed that the Caribbean Salvia arborescens, when provided with a typical moth pollination syndrome, was visited by Celiptera levinum (Lepidoptera: Noctuoidea: Erebidae), which served as a nocturnal pollinator.…”
Section: Introductionmentioning
confidence: 99%